Charge‐Promoted Self‐Metalation of Porphyrins on an Oxide Surface - Egger, Larissa (Angew Chem Int Ed Engl, 2021)
Metalation and self‐metalation reactions of porphyrins on oxide surfaces have recently gained interest. The mechanism of porphyrin self‐metalation on oxides is, however, far from being understood. Herein, we show by a combination of results obtained with scanning tunneling microscopy, photoemission spectroscopy, and DFT computations, that the self‐metalation of 2H‐tetraphenylporphyrin on the surface of ultrathin MgO(001) films is promoted by charge transfer. By tuning the work function of the MgO(001)/Ag(001) substrate, we are able to control the charge and the metalation state of the porphyrin molecules on the surface.